The effects of reduced breathing on swimming performance and on blood lactate concentration in 25 and 50 m breaststroke swimming at maximal intensity - Zompanakis, I.; Papadimitriou, K.; Georgios, T.; Dimitrios, L. (Journal of Swimming Research, 2020)
In Freestyle and the Butterfly stroke, swimmers use the least possible breaths in order to keep their hydrodynamic position and maintain a higher swimming velocity. The purpose of this study was to determine the duration of reduced breathing when swimming Breaststroke affects the hydrodynamic position and preserves the high swimming speed in relation to the production of blood lactate. In this study, 16 swimmers, aged 15.6± 3.2 participated. They swam 25 and 50 m Breaststroke, with breathing frequency for both distances, one breath every stroke (1 on 1) and one breath every three strokes (1 on 3) at high intense. Blood lactate concentration, performance, and efficiency parameters were measured. From the results, swimmers` blood lactate concentration and the time in 25 m between the two breathing frequencies 1 on 1 and 1 on 3, showed a statistically significant difference 10.1 ± 1.8 vs 9.3 ± 1.5 mmol/L (p = 0.02) and 19.5 ± 1.6 vs 19.3 ± 1.6 s (p = 0.03) respectively. In conclusion, in the 25 m distance at maximum intensity, it is preferable to use the 1 on 1 breathing frequency in order to maximize blood lactate concentration, the 1 on 3 breathing frequency in sets of 25 m is more effective at the rate of distances of 100 and 200 m.